Callus Induction from Cotyledon of Gyrinops versteegii (Gilg.) Domke - Fajri Marisa; Lisna Hidayati; Aries Bagus Sasongko; Tri Rini Nuringtyas (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Gyrinops versteegii is an endemic plant in eastern Indonesia that produced agarwood with high quality and economic value. This plant has been threatened by overexploitation which leads on decreasing in the natural population. This research aimed to induce in vitro callus formation to support the sustainable utilization of G. versteegii, which in the end, may support plant productivity. Callus induction was investigated using cotyledon and cultured on MS medium supplemented with several combination of plant growth regulators. The observations were done for the number of explants turned into callus and the duration for the first callus formation. The results showed that combination of 3 mg/L NAA + 0.5 mg/L BAP was recorded as the best combination for callus induction (63.63%). Callus with friable structure and bright color are obtained within nine days of incubation and showed the characteristic of embryonic callus. This result is expected to give a significant opportunity to conserve the natural population of G. versteegii.